PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP BARANG TIRUAN (KW) YANG DIPERJUALBELIKAN DI E-COMMERCE - Qotrunnada, Zumar Salma; Setianingrum, Reni Budi (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
Technological developments due to globalization affect various aspects of life. One of them is in the business world or how transactions have changed. The phenomenon of online transactions through e-commerce allows humans to transact across any boundaries without direct physical contact. However, this also has a negative impact on consumers because of the spread of counterfeit or kw goods that are easily obtained through e-commerce. The reason is that many Indonesians still do not understand the legal validity of the counterfeit goods on the pretext of not being able to buy the original goods so that sometimes it is detrimental to consumers who feel cheated by the seller. This writing examines how legal protection is given to consumers who feel harmed by counterfeit goods traded in e-commerce. Meanwhile, this research uses a type of juridical research sourced from secondary data which includes primary and secondary legal materials.